Improving Elderly Knowledge on Hypertension through Health Education in Parakan Village, Garut - Sadino, Asman; Lubis, Novriyanti; Suryana, Shendi; Prasetiawati, Riska; Hermawan, Belya Anindia; Cahyati, Effan; Apriani, Riza; Karina, Karina; Rena, Rena (Indonesian Journal of Community Empowerment (IJCE), 2025)
Hypertension is a non-communicable disease often referred to as a "silent killer" because it may develop without noticeable symptoms and can lead to serious complications if left untreated. Elderly individuals are among the high-risk groups who require special attention in efforts to prevent and control hypertension. This community service activity aimed to improve the knowledge of elderly residents regarding hypertension through health education as a preventive measure against further complications. The program was conducted in Parakan Village, Garut Regency, involving 30 elderly participants. The method used was health education combined with pre-test and post-test assessments to evaluate knowledge improvement. The results showed a significant increase in understanding after the session, particularly regarding the symptoms and prevention of hypertension. Another notable finding was that most participants had only elementary-level education, which influenced their receptiveness to health information. In conclusion, health education proved effective in enhancing the elderly's knowledge of hypertension and its potential complications. Periodic follow-up education and collaboration with local health services are recommended to sustain the impact.